PENGUNAAN DOSIS PUPUK KANDANG KAMBING DAN WAKTU PEMBERIAN TERHADAP PERTUMBUHAN BIBIT TANAMAN KOPI VARIETAS GAYO 3 (Coffea arabika L.) - Khadijah, Khadijah; Mulyono, Mulyono; Konadi, Sarwan (Universitas Gajah Putih, 2022)
This research aims to determine the influence of coffee plant seedling growth and to determine the interaction effect between these two factors. This research was carried out in the experimental garden of the Faculty of Agriculture, Gajah Putih University, Takengon at an altitude of 1200 above sea level with an optimum pH of 6. The parameters observed consisted of Plant Height at 30, 40 and 50 days after planting, Stem Diameter at 30, 40 and 50 days after planting, Number of Leaves at 30 and 50 days after planting, and Leaf Width at 30, 40 and 50 days after planting. 50 days after planting. The results of the research showed that the use of goat manure dosage and the time of application had a significant effect on plant height at 40 and 50 days after planting and leaf width at 50 days after planting. There was no real interaction between Goat Manure Dosage and Time of Administration in each observation.